Direct Design of Thin and High-Quality Direct-Lit LED Backlight Systems - Zhanghao Ding; Yingli Liu; Yaoguang Ma; Zhenrong Zheng; Min Wang; Ping Zeng; Jun She; Rengmao Wu (IEEE Photonics Journal, 2021)
The direct-lit LED backlight is a key component in large-area LCD displays. The existing methods which rely on point source assumption and irradiance feedback are less effective in compact designs in near field, and designing thin and high-quality back-lit LED backlights still remains a challenging issue. In this paper, we develop a direct method for designing thin and high-quality back-lit LED backlight systems. The étendue of LED light sources is considered in the numerical calculation of the lens profiles without cumbersome Monte Carlo ray tracing, which allows us to obtain compact LED lighting modules and achieve accurate control of the near-field irradiance distribution of the backlight system. Two examples are presented to demonstrate the elegance of this method in designing thin and high-quality back-lit LED backlights.